Assessing avian incubation behavior in response to environmental pollution with temperature-humidity loggers - Freyssinge, Noé; Perkkola, Maria; Leino, Lyydia; Rainio, Miia; Eeva, Tapio (BIRDLIFE FINLAND, 2025)
The negative impact of environmental pollution on avian physiology and breeding success is well documented. However, pollution-related behavioral changes during reproduction remain underexplored, despite behavior often being one of the earliest indicators of environmental disturbances and having significant life-history consequences. For example, altered food availability in a polluted environment could potentially perturb the incubation behavior of income breeders. These birds typically alternate between staying in the nest and heating eggs (on-bout) and taking foraging trips (off-bout). In this two-year study (2020 and 2022), we investigated how the incubation behavior of an insectivorous passerine, the pied flycatcher (Ficedula hypoleuca), varied with environmental pollution levels around a Cu-Ni smelter. Additionally, we compared two different metrics - temperature and humidity within the nest - to evaluate their use as indicators of incubation rhythm. We found that temperature- and humidity-based incubation rhythm parameters correlated, but those based on humidity matched better the true incubation behavior documented by simultaneous video recording. This was because the humidity curve showed a more immediate and intensive response to the female's incubation behavior. Birds in the polluted area took slightly more (11%) but shorter (11%) off-bouts, possibly reflecting smaller energetic constraints or better food availability in the polluted area. However, we found no difference in total incubation intensity between polluted and control areas, with F. hypoleuca females incubating their eggs 75% of the daytime in both environments. Hence, incubating females in the polluted area did not allocate more time for gathering their energy reserves than the birds in the control area, and there was also no difference in the hatching success. Our study is the first to use humidity variation to record incubation rhythm, and our results indicate that measuring humidity inside the nest is a promising technique to test and develop further. types of nests. From an environmental protection standpoint, our results also contribute valuable insights to the relatively limited information on pollution-related behavioral changes.